The Role of Menarcheal Age and Parity in the Development of Uterine Leiomyoma - Elvina Fawwaz Maharizdihar; Yuni Prastyo Kurniati (Journal of Health Sciences and Medical Development, 2025)
Uterine leiomyoma is the most prevalent benign neoplasm of the female reproductive tract during the reproductive years; however, its precise etiology remains incompletely understood. Age at menarche and parity have been proposed as potential risk factors, although previous studies have reported inconsistent findings. This study aimed to evaluate the association between age at menarche and parity with the occurrence of uterine leiomyoma. This research employed a case-control design, in which uterine leiomyoma constituted the case group and adenomyosis served as the control group, conducted at PKU Muhammadiyah Hospital Surakarta. The study included 113 participants, comprising 73 cases of uterine leiomyoma and 40 cases of adenomyosis as controls, identified through histopathological records from 2023. Data were assessed using Chi-Square and logistic regression analyses. The findings revealed that most respondents experienced menarche at a normal age and were either primiparous or multiparous. Statistical testing demonstrated a significant association between age at menarche (p = 0.007; OR = 1.65, 95% CI = 1.414–1.939) and the incidence of uterine leiomyoma, whereas parity was not significantly associated (p = 0.384; OR = 1.509, 95% CI = 0.596–3.825). Future studies are recommended to include more balanced sample group proportions and additional risk factors to obtain a more comprehensive understanding of uterine leiomyoma etiology.